Analysis of the impact of social networks on youth socialization - Sharov, Sergii; Шаров, Сергій Володимирович; Шаров, Сергей Владимирович (My University, 2020)
EN: The article is devoted to consideration of benefits and possible negative impact of the Internet and virtual social networks on socialization of young people. It is mentioned that the problem of socialization of personality in the information society is characterized by a certain contradiction, which is explained by the presence of positive and negative consequences of staying in cyberspace. It is found that the Internet allows us to get many benefits, such as communication over distances, e-commerce, expanding the range of digital services, more active socialization of young people in the digital space, etc. At the same time, possible negative consequences of virtual social networks and the Internet surfing include obsession with anonymity, Internet fraud, lack of social responsibility for antisocial behavior on the Internet, mental, psychological and physical impacts. It has become clear that reduction of the negative impact of the Internet on personality can be implemented due to personal responsibility in cyberspace, compliance with ethical standards and rules of behavior, limiting the time spent on the Internet. UK: Стаття присвячена висвітленню переваг та можливого негативного впливу Internet та віртуальних соціальних мереж на соціалізацію молоді. Зазначається, що проблема соціалізації особистості в умовах інформаційного суспільства характеризується певною суперечністю, яка пояснюється наявністю позитивних та негативних наслідків перебування у віртуальному просторі. Виявлено, що Internet дозволяє отримати багато переваг, таких як спілкування на відстані, електронна комерція, розширення діапазону цифрових послуг, більш активна соціалізація молоді у цифровому просторі та ін. Водночас, до можливих негативних наслідків віртуальних соціальних мереж та серфінгу в Internet можна віднести надмірну захопленість анонімністю, Internet-шахрайство, відсутність соціальної відповідальності за антисоціальні вчинки в Internet, психічні, психологічні та фізичні наслідки. З‟ясовано, що зменшити негативні впливи Internet на особистість можна за рахунок власної відповідальності у віртуальному просторі, дотримання моральних норм та правил поведінки, обмеження часу перебування в Internet.
Аналіз впливу соціальних мереж на соціалізацію молоді
Анализ влияния социальных сетей на социализацию молодежи
Keywords: the Internet; virtual social networks; socialization; social competence; impact; віртуальні соціальні мережі; соціалізація; соціальна компетентність; вплив; виртуальные социальные сети; социализация; социальная компетентность; влияние